Monetary policy and cross-border interbank market fragmentation: Lessons from the crisis - Tobias S. Blattner; Jonathan M. Swarbrick (Bank of Canada, 2020)
We present a two-country model featuring risky lending and cross-border interbank market frictions. We find that (i) the strength of the financial accelerator, when applied to banks operating under uncertainty in an interbank market, will critically depend on the economic and financial structure of the economy; (ii) adverse shocks to the real economy can be the source of banking crisis, causing an increase in interbank funding costs, aggravating the initial shock; and (iii) asset purchases and central bank long-term refinancing operations can be effective substitutes for, or supplements to, conventional monetary policy.
Keywords: E44; E52; F32; F36; 330; Credit and credit aggregates; Business fluctuations and cycles; International financial markets; Transmission of monetary policy; Monetary policy framework